Avoidance of social threat: Evidence from eye movements during a public speaking challenge using 360°- video. (November 2020) - Rubin, Mikael; Minns, Sean; Muller, Karl; Tong, Matthew H.; Hayhoe, Mary M.; Telch, Michael J.
Abstract: Social anxiety (SA) is thought to be maintained in part by avoidance of social threat, which exacerbates fear of negative evaluation. Yet, relatively little research has been conducted to evaluate the connection between social anxiety and attentional processes in realistic contexts. The current pilot study examined patterns of attention (eye movements) in a commonly feared social context – public speaking. Participants ( N  = 84) with a range of social anxiety symptoms gave an impromptu five-minute speech in an immersive 360°-video environment, while wearing a virtual reality headset equipped with eye-tracking hardware. We found evidence for the expected interaction between fear of public speaking and social threat (uninterested vs. interested audience members). Consistent with prediction, participants with greater fear of public speaking looked fewer times at uninterested members of the audience (high social threat) compared to interested members of the audience (low social threat) b  = 0.418, p = 0.046, 95% CI [0.008, 0.829]. Analyses of attentional indices over the course of the speech revealed that the interaction between fear of public speaking and gaze on audience members was only significant in the first three-minutes. Our results provide support for theoretical models implicating avoidance of social threat as a maintaining factor in social anxiety. Future research is needed to test whether guided attentional training targeting in vivo attentional avoidance may improve clinical outcomes for those presenting with social anxiety. Highlights: Realistic 360°-video immersive environment elicits anxiety during a speech. Greater fear of public speaking is linked to specific gaze behaviors. Uninterested (socially threatening) audience members are avoided most. Greater avoidance is linked to greater fear of public speaking. Avoidance fades over the course of the speech.